2011
DOI: 10.1051/apido/2010034
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Nosema ceranae in honey bees in the Balkan countries in the absence of symptoms of colony collapse disorder

Abstract: -Nosema species were determined in honey bees from Balkan countries. A total of 273 Nosemapositive samples were analysed. Duplex PCR and PCR-RFLP with newly designed primers, nos-16S-fw/rv, were used to differentiate between N. apis and N. ceranae. N. apis was detected in only one sample (col-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
83
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 38 publications
10
83
2
4
Order By: Relevance
“…Later Higes et al (2006) reported the presence of N. ceranae infecting A. mellifera in Europe for the first time. Chen et al (2008) collected samples of honey bees between the years 1995 to 2007 and found the pathogen in 12 states in the USA; Liu et al (2008) reported it in China, while other reports over the years include Canada (Williams et al 2008a); Greece (Bacandritsos et al 2010); Thailand (Chaimanee et al 2010); different prefectures in Japan (Yoshiyama and Kimura 2011); several Balkan countries (Stevanovic et al 2011); and Turkey (Whitaker et al 2011). Moreover, Klee et al (2007) reported that N. ceranae is a disease of global proportions detected in many parts of the world, including Europe, Africa, Asia, America and Oceania (Higes et al 2006, Calderón et al 2008, Giersch et al 2009b , Chen and Huang 2010.…”
Section: Discovery and Geographical Distributionmentioning
confidence: 99%
“…Later Higes et al (2006) reported the presence of N. ceranae infecting A. mellifera in Europe for the first time. Chen et al (2008) collected samples of honey bees between the years 1995 to 2007 and found the pathogen in 12 states in the USA; Liu et al (2008) reported it in China, while other reports over the years include Canada (Williams et al 2008a); Greece (Bacandritsos et al 2010); Thailand (Chaimanee et al 2010); different prefectures in Japan (Yoshiyama and Kimura 2011); several Balkan countries (Stevanovic et al 2011); and Turkey (Whitaker et al 2011). Moreover, Klee et al (2007) reported that N. ceranae is a disease of global proportions detected in many parts of the world, including Europe, Africa, Asia, America and Oceania (Higes et al 2006, Calderón et al 2008, Giersch et al 2009b , Chen and Huang 2010.…”
Section: Discovery and Geographical Distributionmentioning
confidence: 99%
“…detection PCR was applied using nos-16S-fw/rv primers [29]. Samples that were confi rmed to be Nosema spp.-positive were subjected to duplex PCR with species-specifi c primers (321APIS-FOR/REV for the detection of N. apis and 218MITOC-FOR/REV for the detection of N. ceranae) designed by Martín-Hernández et al [19] and PCRs were performed the same way as previously described in detail [29]. As positive controls, reference DNA extracts (from bee macerates) of N. apis and N. ceranae, while double-distilled water (ddH 2 O) was the template for the negative control.…”
Section: Nosema Spp Detection and Species Identifi Cationmentioning
confidence: 99%
“…The pathogen is a gram positive, spore forming bacterium Paenibacillus larvae [28]. Traditionally the diagnosis of this disease is based of its specific clinical manifestation.…”
mentioning
confidence: 99%
“…The American foulbrood is highly contagious disease affecting the brood, which inflicts severe economic losses on the beekeeping industry worldwide. The pathogen is a gram positive, spore forming bacterium Paenibacillus larvae [28]. Traditionally the diagnosis of this disease is based of its specific clinical manifestation and cultivation of the pathogen from infected bee colonies.…”
mentioning
confidence: 99%
See 1 more Smart Citation